2022
DOI: 10.1140/epjc/s10052-022-10123-4
|View full text |Cite
|
Sign up to set email alerts
|

Electrically charged quark stars in 4D Einstein–Gauss–Bonnet gravity

Abstract: In this work we study the properties of compact spheres made of a charged perfect fluid with a MIT bag model EoS for quark matter. Considering static spherically symmetric spacetime we derive the hydrostatic equilibrium equations in the recently formulated four dimensional Einstein–Gauss–Bonnet (4D EGB) gravity theory. In this setting, the modified TOV equations are solved numerically with the aim to investigate the impact of electric charge on the stellar structure. A nice feature of 4D EGB theory is that the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 90 publications
1
14
0
Order By: Relevance
“…Furthermore, other spherically symmetric regular solutions were proposed [3][4][5]. There has been tremendous development in the investigations of regular black hole solutions and their properties [6][7][8][9]. Recently, it is observed that regular black hole solutions with spherical symmetry violet the weak energy condition [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, other spherically symmetric regular solutions were proposed [3][4][5]. There has been tremendous development in the investigations of regular black hole solutions and their properties [6][7][8][9]. Recently, it is observed that regular black hole solutions with spherical symmetry violet the weak energy condition [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, black hole solution and their thermal properties have been studied for 4D AdS EGB gravity coupled with Yang-Mills field [16]. Moreover, a black hole solution along with its thermodynamics for 4D EGB gravity [17], 4D EGB massive gravity is presented [18], 4D EGB wormhole solutions [19,20], and 4D EGB quark star [21][22][23][24].…”
mentioning
confidence: 99%
“…The first spherically symmetric regular black hole solution was given by Bardeen [9] that does not hold a strong energy condition. In the recent past, people are paying much attention to the regular black hole solutions [10][11][12][13][14][15][16][17]. An exact regular black hole solution for the EGB coupled with non-Abelian gauge field in 4D AdS spacetime and their thermal properties are explored recently [18].…”
Section: Introductionmentioning
confidence: 99%